Functions of Presynaptic Voltage-gated Calcium Channels. Issue 1 (23rd October 2020) - Dolphin, Annette C
Abstract: Voltage-gated calcium channels are the principal conduits for depolarization-mediated Ca 2+ entry into excitable cells. In this review, the biophysical properties of the relevant members of this family of channels, those that are present in presynaptic terminals, will be discussed in relation to their function in mediating neurotransmitter release. Voltage-gated calcium channels have properties that ensure they are specialized for particular roles, for example, differences in their activation voltage threshold, their various kinetic properties, and their voltage-dependence of inactivation. All these attributes play into the ability of the various voltage-gated calcium channels to participate in different patterns of presynaptic vesicular release. These include synaptic transmission resulting from single action potentials, and longer-term changes mediated by bursts or trains of action potentials, as well as release resulting from graded changes in membrane potential in specialized sensory synapses.